The Effect Of Using Mobile Banking And Religiusity On Consumtive Behavior Of E-Commerce Users - Fathurrahman, Ayif; Febriani, Peggy (Jurnal Ar-Ribh, 2023)
This study aims to determine how the influence of the use of mobile banking and religiosity on the consumptive behavior of SHOPEE e-commerce users, namely Muslim students who use mobile banking in shopping at SHOPEE e-commerce. The sample in this study using purposive sampling technique amounted to 218 respondents. The analytical method used is multiple linear regression analysis. The results of this study indicate that the use of mobile banking has a significant positive effect on the consumptive behavior of SHOPEE e-commerce users, and religiosity has a significant negative effect on the consumptive behavior of SHOPEE e-commerce users